The ego in psychedelic drug action – ego defenses, ego boundaries, and the therapeutic role of regression - Buchborn, Tobias; Kettner, Hannes S.; Kärtner, Laura; Meinhardt, Marcus W. (Frontiers in Neuroscience, 2023)
The ego is one of the most central psychological constructs in psychedelic research and a key factor in psychotherapy, including psychedelic-assisted forms of psychotherapy. Despite its centrality, the ego-construct remains ambiguous in the psychedelic literature. Therefore, we here review the theoretical background of the ego-construct with focus on its psychodynamic conceptualization. We discuss major functions of the ego including ego boundaries, defenses, and synthesis, and evaluate the role of the ego in psychedelic drug action. Along the psycholytic theorem, the psychedelic experience can be conceived of as a functional regression to a developmentally earlier, less structured organization of the ego lacking protection from the ego’s usual defensive apparatus. In such a state, the ego can be brought in contact with repressed emotional themes of significant early life frustrations that have favored the development of maladaptive ego patterns. In frame with psychodynamic thinking, the chronic and habitual patterns in which the ego adapts to the everyday challenges of life, including preferred sets of defenses, is what defines a person’s character. If psychedelic-assisted therapy aims to induce lasting changes to the ego’s adaptive patterns, we argue, it needs to psycholytically permeate and rearrange the characterological core of its habits. The primary working principle of psycholytic therapy therefore is not the state of transient ego regression itself, but rather the regressively favored emotional integration of those early life events that lie at the bottom of a person’s character development. Aiming for increased flexibility of ego patterns, the psycholytic approach is generally compatible with other therapeutic forms of psychedelic-assisted therapy, such as third wave cognitive behavioral approaches